INFLUÃŠNCIA DA Ã‰POCA DE AMOSTRAGEM NA COMPOSIÃ‡ÃƒO QUÃMICA DAS FOLHAS DE GOIABEIRA (Psidium guajava L.) - Natale, William; Coutinho, Edson Luiz Mendes; Boaretto, Antonio Enedi; Banzatto, David Ariovaldo (REVISTA DE AGRICULTURA, 2015)
INFLUÃŠNCIA DA Ã‰POCA DE AMOSTRAGEM NA COMPOSIÃ‡ÃƒO QUÃMICA DAS FOLHAS DE GOIABEIRA (Psidium guajava L.)